Monetary Policy Shocks and Industrial Sector Performance in South Africa - Kutu, Adebayo Augustine; Ngalawa, Harold (Journal of Economics and Behavioral Studies, 2016)
This paper employs an eight variable Structural Vector Auto regression (SVAR) model to examine how monetary policy shocks affect industrial sector performance in South Africa using monthly data from 1994:1 to 2012:12.The study finds no direct link between exchange rate and interest rate shocks and industrial output growth. A money supply shock, however, is observed to exert a significant positive impact on industrial output growth from about the eighth month. The study also reveals that the interest rate response to an unanticipated increase in the rate of inflation is insignificant, reflecting the infrequent changes of the repo rate in the country. We also find evidence of a symbiotic relationship between industrial output growth and other sectors of the economy that form components of aggregate output. The study further demonstrates that monetary authorities have very limited control over industrial output growth using instruments of monetary policy. In addition, it is found that relatively large proportions of the variations in the rate of inflation are explained by changes in money supply, exchange rates and industrial output. We also observe that variations in exchange rates are largely explained by unexpected changes in the exchange rates themselves, which supports the Martingale Hypothesis of exchange rates.